Agriculture on the air - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The BBC World Service broadcasts a weekly programme 'The Farming World' which is of great interest to anyone involved in agricultural extension. It is a programme about making a living from crops, livestock, trees and fish; producing food, fibres,...